2018
DOI: 10.1111/nmo.13284
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term safety and efficacy of acotiamide in functional dyspepsia (postprandial distress syndrome)—results from the European phase 3 open‐label safety trial

Abstract: Backgrounds Acotiamide is a novel acetylcholinesterase inhibitor for treatment of postprandial distress syndrome (PDS) symptoms of functional dyspepsia (FD). This European phase 3 open‐label safety trial has been conducted to evaluate the long‐term safety of acotiamide and explore the efficacy of acotiamide on PDS symptoms using the validated LPDS, quality of life using SF‐36 and SF‐NDI, and work productivity using WPAI. Methods FD‐PDS patients (defined by ROME III criteria) aged ≥18 years with active PDS symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Similarly, the elimination rate of postprandial fullness, upper abdominal bloating and early satiation increased to 12% at week 8 and remained stable thereafter . Similar results were obtained in a European single‐arm 52‐week trial, reporting a moderate or strong improvement of symptoms in 70.2% of the patients . The efficacy of acotiamide to reduce FD symptoms is further supported by several other clinical placebo‐controlled trials, reporting a response rate between 31% and 78% after two or more weeks of treatment .…”
Section: Current Treatment Options For Functional Dyspepsiasupporting
confidence: 78%
“…Similarly, the elimination rate of postprandial fullness, upper abdominal bloating and early satiation increased to 12% at week 8 and remained stable thereafter . Similar results were obtained in a European single‐arm 52‐week trial, reporting a moderate or strong improvement of symptoms in 70.2% of the patients . The efficacy of acotiamide to reduce FD symptoms is further supported by several other clinical placebo‐controlled trials, reporting a response rate between 31% and 78% after two or more weeks of treatment .…”
Section: Current Treatment Options For Functional Dyspepsiasupporting
confidence: 78%
“…92 Acotiamide was also reported to have a significant clinical effect on the quality of life and postprandial symptoms in an open, 3-phase study for long-term outcome and safety. 93 Recently, a study comparing PDS-and EPS-type patients with FD showed that acotiamide significantly improved symptoms in both groups, but in a subgroup analysis, it was found to be more effective against the PDS type. 94 Based on these results, acotiamide would be a good therapeutic agent for patients who primarily have PDS symptoms.…”
Section: Statement 8: Prokinetics Can Be Useful As a First-line Treatmentioning
confidence: 99%
“…These results were reproduced in several physiological clinical studies in FD patients, showing an improvement of gastric accommodation and gastric emptying rate following acotiamide treatment using scintigraphy, ultrasonography or barostat. 15,19,20 Moreover, acotiamide improved FD symptoms after two or more weeks of treatment in comparison to placebo 14,[20][21][22] and was shown to be more effective in the treatment of PDS than EPS. 8 Mechanistic studies in healthy subjects are limited.…”
Section: Introductionmentioning
confidence: 95%